2017
DOI: 10.1159/000455390
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of a Racially Diverse Population with Fibrillary Glomerulonephritis

Abstract: Background: Fibrillary glomerulonephritis is characterized by randomly arranged fibrils, approximately 20 nm in diameter by electron microscopy. Patients present with proteinuria, hematuria and kidney insufficiency, and about half of the reported patients progress to end-stage kidney disease within 4 years. The dependence of patient characteristics and outcomes on race has not been explored. In this study, we describe a cohort of patients with fibrillary glomerulonephritis and compare their clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…However, because diseases other than AAV are sometimes positive for ANCA [13], the interpretation of its staining is difficult except in typical vasculitis. In addition, systemic diseases such as autoimmune diseases, malignant tumors, and chronic infections are known to be associated with 1/3 rd of FGN cases [14]. e pathogenicity of ANCA is thought to be due to differences in its epitopes [15]; however, there is no ideal way to distinguish between them.…”
Section: Discussionmentioning
confidence: 99%
“…However, because diseases other than AAV are sometimes positive for ANCA [13], the interpretation of its staining is difficult except in typical vasculitis. In addition, systemic diseases such as autoimmune diseases, malignant tumors, and chronic infections are known to be associated with 1/3 rd of FGN cases [14]. e pathogenicity of ANCA is thought to be due to differences in its epitopes [15]; however, there is no ideal way to distinguish between them.…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab therapy has recently emerged as a promising alternative therapeutic option to halt the progression of renal disease [ 8 , 9 , 10 ]. A recent study from the University of Northern Carolina showed that of nine rituximab-treated patients, only 11% achieved a stable condition, however those treated earlier and those who had less sclerosis at the time of biopsy responded better to rituximab treatment [ 11 ]. Due to missing data concerning optimal dose of rituximab to treat FGN, our initial protocol (two doses of 375 mg/m 2 separated by one week) was largely extrapolated from the use of rituximab in other glomerular diseases [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solid and hematologic malignancies are common in patients with FGN. 10,13 The prevalence of malignancy in these cohorts have ranged between 4 to 23%. 10,11,13 No causal relationship has been established thus far between malignancy and FGN.…”
Section: Epidemiologymentioning
confidence: 99%
“…10,13 The prevalence of malignancy in these cohorts have ranged between 4 to 23%. 10,11,13 No causal relationship has been established thus far between malignancy and FGN. It is possible that there are coexisting risk factors (such as similar age groups) that increase both the risk of malignancy and FGN.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation